2017
DOI: 10.3906/mat-1604-63
|View full text |Cite
|
Sign up to set email alerts
|

Braided regular crossed modules bifibered over regular groupoids

Abstract: We show that the forgetful functor from the category of braided regular crossed modules to the category of regular (or whiskered) groupoids is a fibration and also a cofibration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Analogous result has appeared in [4,5,6] for the group and groupoid theoretical case and in [7] it is showed that braided regular crossed module of groupoids bifibred over regular groupoids. Also, fibrations of 2crossed modules of groups is given in [8].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Analogous result has appeared in [4,5,6] for the group and groupoid theoretical case and in [7] it is showed that braided regular crossed module of groupoids bifibred over regular groupoids. Also, fibrations of 2crossed modules of groups is given in [8].…”
Section: Introductionsupporting
confidence: 74%
“…for ∈ , , ′ ∈ and * : * ( ) → , * ( ⊗ ) = ( ) is an -algebra morphism and since * ( ⊗ ) so ′ * = * . Thus, we have a cocartesian morphism ( ′ , ) in XMod over : → in -Alg by Proposition [7]. That is, we obtain the following commutative diagram:…”
Section: Examples Of Pullback Crossed Modulesmentioning
confidence: 91%